Gambaran Kadar Hemoglobin dan Indeks Eritrosit pada Wanita Hamil Trimester 3 di Kota Manado - Napitupulu, Raymond K.; Rambert, Glady I.; Berhimpon, Siemona L. E. (Syntax Literate, 2025)
Anggraeny, A., Risanti, E. D., Agustina, T., & Lestari, N. (2023). Correlation of Parity and Maternal Age with the Incidence of Anemia in Pregnant Women. Mutiara Medika: Jurnal Kedokteran Dan Kesehatan, 23(2), 123–128. Cunningham, F. G. (Ed. ). (2022). Williams Obstetrics (Twenty-sixth edition). McGraw-Hill. Fideli, Ü. S., Scher, A. I., Olsen, C., & Hisle-Gorman, E. (2023). Assessing mean corpuscular volume as a screening tool for gestational vitamin B12 deficiency based on NHANES. International Journal for Vitamin and Nutrition Research. Kurniawan, K., Posangi, J., & Rampengan, N. (2017). Association between public knowledge regarding antibiotics and self-medication with antibiotics in Teling Atas Community Health Center, East Indonesia. Medical Journal of Indonesia, 26(1), 62–69. Kurniawan, M. A., & Munandar, A. (2025a). Corporate Social Responsibility, Reputation, and Financial Performance. Syntax Literate; Jurnal Ilmiah Indonesia, 10(4), 3770–3785. Kurniawan, M. A., & Munandar, A. (2025b). Corporate Social Responsibility, Reputation, and Financial Performance. Syntax Literate; Jurnal Ilmiah Indonesia, 10(4), 3770–3785. Kurniawan, M. A., & Munandar, A. (2025c). Corporate Social Responsibility, Reputation, and Financial Performance. Syntax Literate; Jurnal Ilmiah Indonesia, 10(4), 3770–3785. Kusumawati, I., Murti, B., & Pamungkasari, E. P. (2023). Meta-analysis of associations between maternal age, low hemoglobin level during pregnancy, low birth weight, and preterm birth. Journal of Maternal and Child Health, 8(6), 762–775. Lakhiar, K., Shaikh, S. A., Memon, S. F., Nizamani, Y. M., Siddiqui, S., & Hingoro, S. (2024). Red Blood Cell Indices and Morphology in the 3rd Trimester of Pregnant Women Attending Isra University Hospital. Journal of Haematology and Stem Cell Research, 4(1), 171–175. McHugh, A., El-Khuffash, A., Bussmann, N., Doherty, A., Franklin, O., & Breathnach, F. (2019). Hyperoxygenation in pregnancy exerts a more profound effect on cardiovascular hemodynamics than is observed in the nonpregnant state. American Journal of Obstetrics and Gynecology, 220(4), 397-e1. Morton, A. (2021). Haematological normal ranges in pregnancy. Noshiro, K., Umazume, T., Hattori, R., Kataoka, S., Yamada, T., & Watari, H. (2022). Hemoglobin concentration during early pregnancy as an accurate predictor of anemia during late pregnancy. Nutrients, 14(4), 839. Organization, W. H. (2019). WHO benchmarks for International Health Regulations (IHR) capacities. World Health Organization. Putra, I. I., Sondakh, J. M. M., & Kaeng, J. J. (2024). Anemia in pregnancy and its maternal perinatal outcome. Indonesian Journal of Obstetrics and Gynecology, 141–146. Riskesdas, L. N. R. (2018). Jakarta: Lembaga Penerbit Badan Penelitian dan Pengembangan Kesehatan, 2019. Siregar, E. D. P., Amir, A., & Irawati, N. (2022). Correlation between Zinc and Folic Acid Intake with Hemoglobin Levels in Pregnancy. Science Midwifery, 10(5), 3767–3775. Sitorus, E. P. R., Handayani, S., Widayati, R., Fatmaria, F., & Permatasari, S. (2024). The Correlation between Protein, Iron, and Vitamin C Intake with Hemoglobin Levels in Pregnant Women. Mutiara Medika: Jurnal Kedokteran Dan Kesehatan, 24(1), 19–24. World Health Organization. (2018). Healthcare Waste: Key Facts. Who. Wuwungan, G. T., Tinangon, J., & Rondonuwu, S. (2019). Penerapan Metode Value For Money Sebagai Tolok Ukur Penilaian Kinerja Keuangan Pada Organisasi Sektor Publik Di Dinas Kesehatan Kota Manado. Going Concern: Jurnal Riset Akuntansi, 14(4). Zulfiqar, H., Shah, I. U., Sheas, M. N., Ahmed, Z., Ejaz, U., Ullah, I., Saleem, S., Imran, M., Hameed, M., & Akbar, B. (2021). Dietary association of iron deficiency anemia and related pregnancy outcomes. Food Science & Nutrition, 9(8), 4127–4133.